Local government reform in Western Australia: a case study on change readiness - Van Heerden, Vicky (Rhodes University, Faculty of Commerce, Rhodes Business School, 2012)
The Western Australian State Government's local government reform programme, initiated in February 2009, provides the context for this research. Nedlands, a local government in Perth's western suburbs, resolved to participate in this reform programme and signed a Regional Transition Group Agreement with Subiaco local government in August 2010. The purpose of the Regional Transition Group was to prepare a business plan to investigate the potential benefits and viability of a Nedlands and Subiaco amalgamation. Whilst the local government of Nedlands is currently investigating the more operational and technical aspects of local government reform in the merger feasibility study, this research focused on employee readiness, more intangible but no less important. The difficulties of achieving success with organisational change initiatives are well documented. A number of models of planned organisational change have been developed to address these difficulties and support successful change and are outlined. This research highlights the value of the first phase of planned change, namely readiness for change, where organizational members are prepared for and become supporters of change. It also highlights the importance of change communication with respect to developing employee readiness. Definitions and some of the dimensions of 'readiness for change' are outlined. The five dimensions of readiness for change - discrepancy, appropriateness, principal support, efficacy and valence - provide the 'lens' through which readiness for change at Nedlands is explored. From this perspective, the documentation communicating local government reform at Nedlands was analysed. These dimensions were also used to ascertain, from the perspective of the Nedlands' managers, their level of readiness and the readiness of the employees of Nedlands for local government reform. The findings suggest that Nedlands local government has not consciously planned to 'ready' employees for local government reform. A number of management recommendations are made to strengthen the change readiness message communicated by the Nedlands local government and to support the development of the Nedlands employees' readiness for change.
Keywords: Local government -- Australia -- Nedlands (W.A.); Local government -- Australia -- Subiaco (W.A.); Organizational change -- Australia -- Nedlands (W.A.); Local officials and employees -- Australia -- Nedlands (W.A.); Industrial relations -- Australia -- Nedlands (W.A.); Industrial management -- Australia -- Nedlands (W.A.); Corporate culture -- Australia -- Nedlands (W.A.)